Implementation of The Corporate University (Corpu) in Enhancing Employee Competencies at The Cirebon Regency Human Resources Development Agency - Elga Lauza Evelyna; Yanto Heryanto (Journal Of Social Science (JoSS), 2026)
This study was motivated by the quality of civil servant resources at the Personnel and Human Resources Development Agency in Cirebon Regency. The purpose of this study was to determine and analyze the impact of improving the competence of civil seravants after the implementation of Corporate University at PHRDA in Cirebon Regency in 2024. The research method used was qualitative with a descriptive analysis approach using Spencer & Spencer's (1993) theory, which focuses on five indicators: (1) Knowledge, (2) Skills, (3) Self-Concept, (4) Traits, and (5) Motives. The results of the study indicate that employee competency through the implementation of Corporate University in PHRDA of Cirebon Regency has produced fairly good results with a gradual increase in the competency of civil servants through changes in the technology-based learning culture produced by CorpU, but still faces a number of challenges in terms of infrastructure. In addition, in its implementation, some PHRDA employees in Cirebon Regency have not fully mastered digital literacy and still need to adjust to adapt to the dynamics of a flexible work environment. The conclusion of this study is that some civil servants in Cirebon Regency have kept up with the technological advances produced by CorpU, and despite obstacles, the PHRDA of Cirebon Regency is striving to provide solutions through Training Program so that CorpU can be implemented optimally within the civil service of Cirebon Regency.